2011
DOI: 10.1021/ja207680e
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Sensors Based on Fluorous Membranes Doped with Highly Selective Ionophores for Carbonate

Abstract: Manganese(III) complexes of three fluorophilic salen derivatives were used to prepare ion-selective electrodes (ISEs) with ionophore-doped fluorous sensing membranes. Because of their extremely low polarity and polarizability, fluorous media are not only chemically very inert but also solvate potentially interfering ions poorly, resulting in a much improved discrimination of such ions. Indeed, the new ISEs exhibited selectivities for CO32− that exceed those of previously reported ISEs based on non-fluorous mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 67 publications
0
43
0
Order By: Relevance
“…This method 29,53,54 was already used in the past to determine complex stabilities in fluorous membranes. 43,45,48 For the purpose of this work, tetraphenylphosphonium (PPh 4 + ) was chosen as the ion that does not form complexes with the ionophore.…”
Section: Resultsmentioning
confidence: 99%
“…This method 29,53,54 was already used in the past to determine complex stabilities in fluorous membranes. 43,45,48 For the purpose of this work, tetraphenylphosphonium (PPh 4 + ) was chosen as the ion that does not form complexes with the ionophore.…”
Section: Resultsmentioning
confidence: 99%
“…We found that fluorous systems exhibit substantially improved ion selectivities as compared to non‐fluorous ISE membranes, which has also resulted in remarkably low detection limits . Electrodes with fluorous membranes have been successfully applied for the detection of several analytes, not only in simple aqueous samples but also in biologically relevant systems such as bacterial growth media, lake and river water containing natural organic matter, and Ottawa Sand suspensions . Here we discuss the lifetime of pH sensors with ionophore‐doped fluorous sensing membranes when exposed to hot caustic solutions as they are used in CIP treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In pure form, such salts were described as 'frozen ionic liquids' with appreciable fluorescence, which confirms that the counterion can prevent p-stacking of the dyes 25,26 . The tetraphenyl borate (TPB) anion and its fluorinated analogues, used as ionophores in polymeric cation-sensitive electrodes 27,28 , are particularly interesting counterions due to their bulky tetrahedral structure. However, so far, no attempts were made to use TPBs for encapsulation of cationic dyes into polymer NPs.…”
mentioning
confidence: 99%